Subsurface modified enhanced conductive liquid crystal elastomer fiber as well as preparation method and application thereof
By grafting the polymer brush on the sub-surface of the liquid crystal elastomer fiber and performing metal electrodeposition, forming a wrinkled metal coating and applying a waterproof layer, the problems of insufficient interface binding force and poor conductivity in the liquid crystal elastomer fiber driving technology are solved, and fast response, sensitive sensing and high conductivity are achieved.
Patent Information
- Application Number
- CN202510738262.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-08-01
AI Technical Summary
The existing liquid crystal elastomer fiber drive technology has problems such as insufficient interface binding force, poor conductivity stability, limited response speed and low driving control accuracy, especially under large strain cycles, performance is significantly reduced.
The polymer brushes are grafted on the subsurface of the liquid crystal elastomer fibers and metal electrodeposition is performed after ion exchange in ammonium tetrachloropalladium solution to form a wrinkled metal coating, and then coated with the Ecoflex waterproof layer to achieve strong interface bonding and conductive stability.
It realizes a strong interface combination between the conductive layer and the substrate, has good conductivity stability, can maintain a complete structure under multiple drives, has fast response and sensitive sensing functions, and prevents electrochemical corrosion and maintains the deformation ability of the fiber.
Smart Images

Figure CN120401228A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid crystal elastomer fibers, and particularly relates to a subsurface modified enhanced conductive liquid crystal elastomer fiber, a preparation method thereof and an application thereof. Background Art
[0002] The requirements for the core driving materials of soft robots are increasing day by day. As the key execution unit of soft robots, artificial muscle fibers need to have characteristics such as fast response, large strain output, high flexibility and precise controllability, so as to achieve efficient, low-noise and high-degree-of-freedom driving functions. Liquid crystal elastomer (LCE) fibers are regarded as ideal substrates for artificial muscle fibers due to their high reversible deformation ability, excellent mechanical properties and thermoactuation effect brought by the molecular chain orientation characteristics. However, there are still significant bottlenecks in the existing LCE fiber driving technology, which seriously restricts its practical application. The driving mechanism of LCE fibers mostly depends on environmental temperature, light field or humidity changes. Such passive triggering methods result in slow driving response (usually at the minute level), poor controllability and difficulty in integrating a closed-loop feedback system. To improve functionality, some studies have doped materials such as carbon nanotubes and conductive polymers into the LCE fiber matrix to introduce an electro-driven response. However, this method faces two challenges: First, the interfacial compatibility between the dopant and the LCE fiber matrix is poor, resulting in stress concentration inside the material, a significant reduction in driving strain (usually less than 30%), and the cyclic life is also affected; Second, the doping triggering mechanism needs to rely on the overall material to be heated by electricity, and the response speed is limited, making it difficult to meet the high-frequency driving requirements.
[0003] To address the above problems, recent research has turned to surface functionalization strategies. For example, a conductive layer (such as silver nanowires, graphene film) is coated on the surface of LCE fibers to achieve electro-triggered driving through the Joule heating effect. However, there is a significant problem of insufficient interfacial bonding force between the conductive layer prepared by traditional coating processes (such as dipping, spraying) and the LCE fiber matrix: On the one hand, the surface energy of LCE fibers is low and lacks active functional groups, resulting in difficulty for the conductive layer to achieve strong adhesion through chemical bonding, and only relying on physical adsorption is prone to slip or peel off during dynamic deformation; On the other hand, the modulus difference between the conductive layer and the LCE matrix is huge (the modulus of the conductive layer is usually higher than 1 GPa, while the modulus of the LCE matrix is only several MPa to hundreds of MPa). During repeated driving, the interfacial shear stress increases sharply, and the conductive layer is prone to crack or peel off, seriously affecting the driving stability and signal transmission reliability. In addition, the weak interfacial bonding between the conductive layer and the matrix will also cause local resistance mutation during the dynamic response process, further reducing the accuracy and repeatability of driving control.
[0004] More critically, the existing surface conductive layer exhibits serious conductive stability defects in dynamic driving scenarios: when the LCE fiber undergoes large-strain cycling, microcrack propagation occurs in the conductive layer due to the lack of elastic deformation ability, and its resistance value increases exponentially with the number of cycles, resulting in the attenuation of Joule heat efficiency and the decrease of driving response speed. In addition, the difference in the thermal expansion coefficients between the conductive layer and the fiber matrix will cause interfacial thermal stress during temperature changes, exacerbating the fracture of the conductive network and further weakening the driving performance and lifespan. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a subsurface-modified enhanced conductive liquid crystal elastomer fiber and its preparation method and application. The subsurface-modified enhanced conductive liquid crystal elastomer fiber of the present invention has a strong interfacial bonding force between the conductive layer and the matrix and good conductive stability.
[0006] The present invention provides a preparation method for a subsurface-modified enhanced conductive liquid crystal elastomer fiber, comprising the following steps:
[0007] Mix a liquid crystal monomer, a crosslinking agent, a spacer, a non-polar solvent, an atom transfer radical polymerization initiator, an amine catalyst, and a photoinitiator to carry out a first crosslinking reaction, remove the solvent from the obtained first crosslinking reaction solution, and carry out a second crosslinking reaction under ultraviolet light irradiation and stretching to obtain a liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator;
[0008] Under a protective atmosphere, mix the liquid crystal elastomer fiber containing the atom transfer radical polymerization initiator, methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, CuBr, and methanol to carry out an atom transfer radical polymerization reaction to obtain a liquid crystal elastomer fiber with a subsurface grafted polymer brush;
[0009] Carry out ion exchange on the liquid crystal elastomer fiber with the subsurface grafted polymer brush in an ammonium tetrachloropalladate solution to obtain a liquid crystal elastomer fiber with active sites on the surface;
[0010] Carry out electroless metal deposition on the liquid crystal elastomer fiber with active sites on the surface to obtain a liquid crystal elastomer fiber with a wrinkled metal coating;
[0011] Coat an Ecoflex waterproof layer on the surface of the liquid crystal elastomer fiber with the wrinkled metal coating to obtain a subsurface-modified enhanced conductive liquid crystal elastomer fiber.
[0012] Preferably, the mass of the atom transfer radical polymerization initiator is 3% - 8% of the total mass of the liquid crystal monomer, crosslinking agent, spacer, non-polar solvent, amine catalyst, and photoinitiator.
[0013] Preferably, the temperature of the atom transfer radical polymerization reaction is 50 - 70 °C, and the time is 4 - 5 h.
[0014] Preferably, the dosage ratio of methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, and CuBr is 5 mL: 126-128 mg: 67-68 mg.
[0015] Preferably, the ion exchange in the ammonium tetrachloropalladate solution is as follows: soaking the liquid crystal elastomer fiber with the subsurface grafted polymer brush in the ammonium tetrachloropalladate solution; the concentration of the ammonium tetrachloropalladate solution is 5-10 mmol / L, and the soaking time is 2-6 h.
[0016] Preferably, the electroless metal deposition is as follows: soaking the liquid crystal elastomer fiber with active sites on the surface in the metal solution; the metal solution includes electroless copper plating solution, electroless nickel plating solution, electroless silver plating solution, or electroless gold plating solution; the soaking time is 30-180 min.
[0017] Preferably, the electroless copper plating solution includes solution A and solution B. Solution A includes: 13 g / L copper sulfate pentahydrate, 29 g / L sodium potassium tartrate, 12 g / L sodium hydroxide, and 1 g / L dimethylaminoborane; solution B is an aqueous formaldehyde solution with a concentration of 0.35-0.38 wt%; the volume ratio of solution A to solution B is 1:1.
[0018] Preferably, the coating of the Ecoflex waterproof layer is as follows: immersing the liquid crystal elastomer fiber with a wrinkled metal coating in the Ecoflex solution, lifting, and curing; the solid content of the Ecoflex solution is 18%-22%.
[0019] The present invention also provides a subsurface modified enhanced conductive liquid crystal elastomer fiber obtained by the preparation method of the above technical solution, including a liquid crystal elastomer fiber and a polymer brush grafted on the subsurface of the liquid crystal elastomer fiber, as well as a wrinkled metal coating and an Ecoflex waterproof layer sequentially arranged on the surface of the polymer brush.
[0020] The present invention also provides an application of the subsurface modified enhanced conductive liquid crystal elastomer fiber of the above technical solution in a soft robot.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a preparation method of a subsurface-modified enhanced conductive liquid crystal elastomer fiber. After grafting a polymer brush on the subsurface of the liquid crystal elastomer fiber, ion exchange is carried out in an ammonium tetrachloropalladate solution, and the surface of the liquid crystal elastomer fiber will automatically swell. A metal coating is electrolessly deposited on the metal, and wrinkles are automatically generated. The prepared subsurface-modified enhanced conductive liquid crystal elastomer fiber has good conductivity and excellent driving performance. Under the action of the embedded polymer brush, a strong interfacial bond is formed between the metal coating and the fiber matrix, and the complete structure and excellent conductive performance can be maintained under multiple cyclic driving, and the conductive stability is good. At the same time, after the modified subsurface layer is damaged, polymerization modification can be repeatedly initiated without initiator modification and assembly. In addition, since the metal particles in the wrinkled structure are in contact with each other to form a conductive path, sensitive electrical signal changes can achieve precise sensing functions. The present invention adds an Ecoflex waterproof layer on the surface of the metal coating, which can effectively isolate environmental moisture and electrolytes, prevent the electrochemical corrosion of the metal coating, and at the same time, maintain the original driving performance of the fiber and will not affect the deformation ability of the LCE fiber. Description of the Drawings
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0024] Figure 1 It is a flow chart of the preparation method of the subsurface-modified enhanced conductive liquid crystal elastomer fiber of the present invention;
[0025] Figure 2 It is a scanning electron microscope (SEM) image of the as-prepared primary LCE fiber containing an ATRP initiator in Example 1;
[0026] Figure 3 It is a polarized light microscope (POM) image of the as-prepared primary LCE fiber containing an ATRP initiator in Example 1;
[0027] Figure 4 It is an SEM image of the LCE composite fiber prepared in Example 1;
[0028] Figure 5 It is an SEM image of the LCE composite fiber prepared in Example 2;
[0029] Figure 6 It is an SEM image of the LCE composite fiber prepared in Example 3;
[0030] Figure 7The maximum braking strain diagram of the LCE composite fiber prepared in Example 1 at different voltages when a 5.5 g heavy object is loaded;
[0031] Figure 8 The braking strain diagram of the LCE composite fiber prepared in Example 1 at different temperatures;
[0032] Figure 9 The result diagram of the LCE composite fiber prepared in Example 1 after 500 cycles under electrothermal drive at 20 V for 0.1 s. Detailed implementation mode
[0033] The present invention provides a preparation method for a subsurface-modified enhanced conductive liquid crystal elastomer fiber, comprising the following steps:
[0034] Mix a liquid crystal monomer, a crosslinking agent, a spacer, a nonpolar solvent, an atom transfer radical polymerization initiator, an amine catalyst, and a photoinitiator to carry out a first crosslinking reaction, remove the solvent from the obtained first crosslinking reaction solution, and carry out a second crosslinking reaction under ultraviolet light irradiation and stretching to obtain a liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator;
[0035] Under a protective atmosphere, mix the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator, methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, CuBr, and methanol to carry out an atom transfer radical polymerization reaction to obtain a liquid crystal elastomer fiber with a subsurface grafted polymer brush;
[0036] Carry out ion exchange on the liquid crystal elastomer fiber with a subsurface grafted polymer brush in an ammonium tetrachloropalladate solution to obtain a liquid crystal elastomer fiber with active sites on the surface;
[0037] Carry out electroless metal deposition on the liquid crystal elastomer fiber with active sites on the surface to obtain a liquid crystal elastomer fiber with a wrinkled metal coating;
[0038] Coat an Ecoflex waterproof layer on the surface of the liquid crystal elastomer fiber with a wrinkled metal coating to obtain a subsurface-modified enhanced conductive liquid crystal elastomer fiber.
[0039] In the present invention, unless otherwise specified, the materials and equipment used are all commercially available products in the art.
[0040] The present invention mixes a liquid crystal monomer, a crosslinking agent, a spacer, a nonpolar solvent, an atom transfer radical polymerization initiator, an amine catalyst, and a photoinitiator to carry out a first crosslinking reaction, removes the solvent from the obtained first crosslinking reaction solution, and carries out a second crosslinking reaction under ultraviolet light irradiation and stretching to obtain a liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator.
[0041] In the present invention, the liquid crystal monomer is preferably 2-methyl-1,4-phenylene bis(4-(3-(acryloyloxy)propoxy)benzoate (RM257).
[0042] In the present invention, the crosslinking agent is preferably pentaerythritol tetra-3-mercaptopropionate (PETMP).
[0043] In the present invention, the spacer is preferably 3,6-dioxa-1,8-octanedithiol (EDDET) or 1,6-hexanedithiol (HDT).
[0044] In the present invention, the atom transfer radical polymerization (ATRP) initiator is preferably 2-(2-bromoisobutyryloxy)ethyl methacrylate (BrMA).
[0045] In the present invention, the non-polar solvent preferably includes toluene or dichloromethane.
[0046] In the present invention, the mixing of the liquid crystal monomer, crosslinking agent, spacer, non-polar solvent, atom transfer radical polymerization initiator, amine catalyst and photoinitiator is preferably as follows: the liquid crystal monomer, crosslinking agent, spacer and non-polar solvent are first mixed to obtain a mixed solution, and then the atom transfer radical polymerization initiator, amine catalyst and photoinitiator are added; the first mixing is preferably carried out under stirring. The mixing method described in the present invention can ensure the uniform dispersion of each component, thereby obtaining a uniform mixed solution.
[0047] In the present invention, the mass ratio of the liquid crystal monomer in the liquid crystal monomer, crosslinking agent, spacer and non-polar solvent (mixed solution) is preferably 19% to 60%, specifically it can be 19% or 59%.
[0048] In the present invention, the mass ratio of the crosslinking agent to the spacer is preferably 2:9 or 2.9:2.7.
[0049] In the present invention, the mass of the atom transfer radical polymerization initiator is preferably 3% to 8% of the total mass of the liquid crystal monomer, crosslinking agent, spacer, non-polar solvent, amine catalyst and photoinitiator, specifically it can be 5%. The mass ratio described in the present invention is beneficial to the growth of the polymer brush.
[0050] In the present invention, the amine catalyst is preferably dipropylamine (DPA); the dipropylamine is preferably used in the form of a dipropylamine toluene solution, and the volume ratio of dipropylamine to toluene in the dipropylamine toluene solution is preferably 1:50; the mass ratio of the liquid crystal monomer to the dipropylamine toluene solution is preferably 4:0.5 to 0.6; the dipropylamine toluene solution is preferably added dropwise to the mixed solution.
[0051] In the present invention, the photoinitiator is preferably (2-hydroxyethoxy)-2-methylpropiophenone (HHMP).
[0052] In the present invention, the temperature of the first cross-linking reaction is preferably room temperature, specifically 20 °C or 25 °C, and the time is preferably 3 - 10 min. During the first cross-linking reaction, the cross-linking agent and the liquid crystal monomer react to form a cross-linked network. The spacer adjusts the distance between liquid crystal molecules. The photoinitiator (HHMP) will absorb ultraviolet light in the next step and undergo photolysis to generate free radicals, which initiate the polymerization reaction of RM257 to form a network structure. Specifically, the first cross-linking reaction is a Michael addition reaction, mainly the carbon-carbon double bond of the acrylate of the liquid crystal monomer RM257 and the mercapto groups of the cross-linking agent PETMP and the spacer such as EDDET react under the action of the amine catalyst DPA to form a cross-linked network.
[0053] In the present invention, the removal of the solvent is preferably carried out in a polytetrafluoroethylene (PTFE) mold. The removal of the solvent is preferably by heating and evaporation. The temperature of the heating and evaporation is preferably 80 °C, and the time is preferably 24 h.
[0054] In the present invention, the draw ratio of the stretching is preferably 2.5 - 3 times.
[0055] In the present invention, the wavelength of the ultraviolet light used in the second cross-linking reaction is 320 nm - 500 nm, specifically 365 nm. The temperature is preferably room temperature, specifically 20 °C or 25 °C, and the time is preferably 3 - 5 min. Under the action of ultraviolet light irradiation in the second cross-linking reaction, the liquid crystal units will be oriented to obtain a liquid crystal elastomer fiber (LCE fiber containing ATRP initiator) with a fixed orientation of liquid crystal units and molecular chain arrangement and containing an atom transfer radical polymerization initiator. Specifically, during the stretching and ultraviolet light irradiation process, the photoinitiator HHMP absorbs ultraviolet energy and cleaves to generate free radicals, which polymerize with the carbon-carbon double bond of the acrylate of the unreacted liquid crystal monomer RM257 to form the second cross-linking reaction.
[0056] After obtaining the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator, in the present invention, under a protective atmosphere, the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator, methacryloyloxyethyltrimethylammonium chloride, 2,2-bipyridine, CuBr and methanol are mixed to carry out an atom transfer radical polymerization reaction to obtain a liquid crystal elastomer fiber with a subsurface grafted polymer brush.
[0057] In the present invention, the protective atmosphere is preferably a nitrogen atmosphere.
[0058] In the present invention, the volume ratio of methacryloyloxyethyltrimethylammonium chloride (METAC) to methanol is preferably 1:1.
[0059] In the present invention, the mass ratio of the 2,2-bipyridine to CuBr is preferably 126 - 128:67 - 68.
[0060] In the present invention, the dosage ratio of the methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, and CuBr is preferably 5 mL:126 - 128 mg:67 - 68 mg.
[0061] In the present invention, the mixing of the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator, methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, CuBr, and methanol is preferably as follows: soaking the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator in a mixed solution of methacryloyloxyethyl trimethyl ammonium chloride solution, 2,2-bipyridine, CuBr, and methanol. The temperature of the atom transfer radical polymerization (ATRP) reaction is preferably 50 - 70 °C, specifically it can be 60 °C, and the time is preferably 4 - 5 h, specifically it can be 4.5 h; the ATRP reaction is preferably carried out under stirring, and the stirring rate is preferably 200 rpm.
[0062] In the present invention, when mixing the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator, methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, CuBr, and methanol, sodium perchlorate is preferably added to accelerate the reaction rate. The dosage ratio of methacryloyloxyethyl trimethyl ammonium chloride to sodium perchlorate is preferably 5 mL:139 - 140 mg.
[0063] METAC is the reaction monomer, CuBr is the catalyst, and 2,2-bipyridine is the ligand. The ligand will react with the catalyst to form a complex, and then react with the LCE fiber containing the ATRP initiator. Through halogen atom transfer, free radicals are generated to initiate the polymerization of the METAC monomer. The free radicals continuously react with the monomer to form a polymer chain, and finally a dense polymer brush is formed. In the present invention, the subsurface (tens of micrometers below the fiber surface) of the LCE fiber containing the ATRP initiator is modified by the ATRP reaction to form a surface structure that is more likely to capture the cationic catalyst.
[0064] In the present invention, after the atom transfer radical polymerization reaction, washing and drying are preferably further included; the washing reagent is preferably methanol or deionized water; the drying is preferably carried out in a protective atmosphere.
[0065] In the present invention, the polymer brush is preferably on the micron scale, specifically, for example, the length on the fiber surface is 10 - 20 micrometers.
[0066] After obtaining the liquid crystal elastomer fibers with subsurface grafted polymer brushes, the present invention performs ion exchange on the liquid crystal elastomer fibers with subsurface grafted polymer brushes in an ammonium tetrachloropalladate solution to obtain liquid crystal elastomer fibers with active sites on the surface.
[0067] In the present invention, the ion exchange in the ammonium tetrachloropalladate solution is preferably: immersing the liquid crystal elastomer fibers with subsurface grafted polymer brushes in the ammonium tetrachloropalladate solution; the concentration of the ammonium tetrachloropalladate solution is preferably 5 - 10 mmol / L, and the immersion time is preferably 0.5 - 6 h, specifically it can be 1 h or 2 h. The quaternary ammonium group (-N(CH3) 3+ ) on the polymer brush surface makes the surface of the polymer brush positively charged, and its counter ion is Cl - . During the immersion process, ammonium tetrachloropalladate hydrolyzes in water to produce [PdCl4] 2- , and Cl - undergoes ion exchange with [PdCl4] 2- to make the surface of the LCE fibers have catalytic active sites, and at the same time the fiber surface swells.
[0068] In the present invention, after the ion exchange, washing is preferably further included, and the washing is preferably water washing.
[0069] After obtaining the liquid crystal elastomer fibers with active sites on the surface, the present invention performs electroless metal deposition on the liquid crystal elastomer fibers with active sites on the surface to obtain liquid crystal elastomer fibers with a wrinkled metal coating.
[0070] In the present invention, the electroless metal deposition is preferably: immersing the liquid crystal elastomer fibers with active sites on the surface in a metal solution; the metal solution preferably includes a copper electroless plating solution, a nickel electroless plating solution, a silver electroless plating solution, or a gold electroless plating solution;
[0071] The copper electroless plating solution preferably includes solution A and solution B. Solution A includes: 13 g / L copper sulfate pentahydrate, 29 g / L sodium potassium tartrate, 12 g / L sodium hydroxide, and 1 g / L dimethylaminoborane; solution B is preferably a 0.35 - 0.38 wt% aqueous formaldehyde solution; the volume ratio of solution A to solution B is preferably 1:1;
[0072] The nickel electroless plating solution preferably includes a mixed solution and a reducing agent solution. The mixed solution includes: 900 mL deionized water, 40 g nickel sulfate hexahydrate, 20 g sodium citrate, and 10 g lactic acid; the reducing agent solution is a 3 - 10 g / L dimethylaminoborane solution; the mass ratio of the mixed solution to the dimethylaminoborane solution is 4:1; when in use, the pH value of the nickel electroless plating solution is adjusted to 8 - 9 with ammonia water;
[0073] The silver electroless plating solution preferably comprises: 17 g / L of AgNO3, 1 mol / L of NH3, 0.5 wt% of PVP, 0.5 wt% of ethylenediamine, and 30 g / L of glucose;
[0074] The gold electroless plating solution preferably comprises: 4.7 g / L of potassium chloroaurate, 15.8 g / L of sodium thiosulfate, 12.6 g / L of sodium sulfite, 2.6 g / L of ammonium chloride, and 39.2 g / L of L - malic acid sodium.
[0075] The time for electroless deposition (immersion) of the metal is preferably 30 - 180 min, specifically it can be 120 min. After immersion in the metal solution, palladium acts as a catalyst to activate the reducing agent (such as formaldehyde) to reduce metal ions (such as copper) in the solution into metal, so as to deposit a metal layer on the surface of the LCE fiber, forming a metal coating with high interfacial adhesion fastness on the surface of the LCE fiber. The swelling will retract during this process, forming a wrinkled - structure metal coating.
[0076] After obtaining the liquid - crystal elastomer fiber with a wrinkled metal coating, the present invention coats an Ecoflex waterproof layer on the surface of the liquid - crystal elastomer fiber with a wrinkled metal coating to obtain a sub - surface modified enhanced - conductive liquid - crystal elastomer fiber.
[0077] In the present invention, the coating of the Ecoflex waterproof layer is preferably as follows: immersing the liquid - crystal elastomer fiber with a wrinkled metal coating into an Ecoflex (butylene terephthalate - adipate) solution, pulling it up, and curing. The Ecoflex solution preferably comprises Ecoflex 00 - 30 silicone rubber, a curing agent, and an organic solvent; the mass ratio of the Ecoflex 00 - 30 silicone rubber to the curing agent is preferably 10:1, the organic solvent is preferably tetrahydrofuran, the solid content of the Ecoflex solution is preferably 18% - 22%, specifically it can be 20%. The pulling - up is preferably uniform pulling - up, and the rate of the pulling - up is preferably 0.5 mm / s. The curing is preferably carried out at room temperature, and the time is preferably 24 h. The sub - surface modified enhanced - conductive liquid - crystal elastomer fiber is a wrinkled - metal - coated LCE fiber with waterproof function and high interfacial adhesion fastness.
[0078] In the present invention, the thickness of the Ecoflex waterproof layer is preferably 50 - 100 μm, specifically it can be 80 μm.
[0079] The present invention also provides a sub - surface modified enhanced - conductive liquid - crystal elastomer fiber obtained by the preparation method of the above - mentioned technical solution, which comprises a liquid - crystal elastomer fiber, a polymer brush grafted on the sub - surface of the liquid - crystal elastomer fiber, and a wrinkled metal coating and an Ecoflex waterproof layer sequentially arranged on the surface of the polymer brush.
[0080] The present invention also provides an application of the subsurface-modified enhanced conductive liquid crystal elastomer fiber described in the above technical solution in a soft robot.
[0081] The subsurface-modified enhanced conductive liquid crystal elastomer fiber of the present invention can be widely applied to cutting-edge fields such as high-precision joint driving of soft robots, real-time deformation sensing of flexible electronic devices, dynamic signal capture of biomedical sensors, and stress-electric signal coupling regulation of bionic muscles in tissue engineering.
[0082] The present invention provides a preparation method of a subsurface-modified enhanced conductive liquid crystal elastomer fiber. By grafting polymer brushes on the subsurface, the conductive layer of the prepared LCE composite fiber forms a strong interfacial bond with the fiber matrix through embedded polymer brushes, endowing the fiber surface modification layer with better mechanical properties. And after the modified subsurface layer is damaged, polymerization modification can be repeatedly initiated without initiator modification and assembly. At the same time, based on the dynamic bridging effect of metal particles at the wrinkled structure, the fiber can achieve rapid response and sensitive sensing. After multiple driving cycles, it still exhibits excellent driving performance, high conductivity, and good mechanical properties.
[0083] To further illustrate the present invention, the subsurface-modified enhanced conductive liquid crystal elastomer fiber, its preparation method and application provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0084] Figure 1 The figure is a flowchart of the method for preparing the subsurface-modified enhanced conductive liquid crystal elastomer fiber. S1: Prepare an LCE fiber (soft actuator) containing an atom transfer radical polymerization initiator; S2: Initiate atom transfer radical polymerization on the subsurface to graft micron-scale polymer brushes; S3: Perform catalyst ion exchange treatment; S4: Carry out electroless metal deposition to obtain a wrinkled metal-coated LCE fiber; S5: Coat an Ecoflex waterproof layer on the metal coating surface to obtain a wrinkled metal-coated LCE fiber with waterproof function and high interfacial adhesion strength.
[0085] Example 1
[0086] Step S1: Add 4 g of liquid crystal monomer (RM257) to 1.6 g of toluene, and heat and dissolve it at 80°C. After cooling to room temperature, add 0.2 g of crosslinking agent (PETMP) and 0.9 g of spacer (EDDET) to obtain a mixed solution.
[0087] Subsequently, 0.36 g of an ATRP initiator (BrMA) was added to the mixed solution, and a dipropylamine (DPA) solution (diphenylamine was diluted with toluene at a volume ratio of 1:50, and the total mass of dipropylamine and toluene was 0.56 g) and 0.02 g of a photoinitiator (HHMP) were added. The solution was injected into a polytetrafluoroethylene (PTFE) mold and reacted at room temperature for 3 min. The solvent was evaporated at 80 °C for 24 h, the PTFE mold was removed, and then ultraviolet curing was carried out at a stretching ratio of 2.5 times (wavelength 365 nm, time 3 min) to complete the second cross-linking, obtaining LCE fibers containing an ATRP initiator (as-prepared LCE fibers).
[0088] Step S2: Dissolve 5 mL of METAC in 5 mL of methanol at 20 °C, then add 127.6 mg of 2,2-bipyridine, 67.6 mg of CuBr, and the LCE fibers containing an ATRP initiator prepared in Step S1 to the solution, with the temperature at 60 °C and the stirring rate at 200 rpm, and polymerize for 4.5 h under nitrogen protection;
[0089] The polymerized LCE fibers were rinsed with methanol and dried under a protective atmosphere to obtain LCE fibers with sub-surface grafted micro-scale polymer brushes.
[0090] Step S3: Immerse the LCE fibers with sub-surface grafted micro-scale polymer brushes in an aqueous solution of 5 mM ammonium tetrachloropalladate for 1 h for ion exchange;
[0091] Wash with clean water to obtain LCE fibers with a swollen surface and catalytic active sites.
[0092] Step S4: Immerse the LCE fibers with a swollen surface and catalytic active sites treated in Step S3 in a copper electroless plating solution obtained by mixing solution A (13 g / L copper sulfate pentahydrate, 29 g / L potassium sodium tartrate, 12 g / L sodium hydroxide, and 1 g / L dimethylaminoborane) and solution B (take 9.5 mL of 37.0 - 40.0 wt% AR grade formaldehyde solution and dilute it to 1 L) at a volume ratio of 1:1 for 120 min (metal electroless deposition), and the swelling will retract to form a wrinkled structure during this process, obtaining LCE fibers with a wrinkled metal coating having high interfacial adhesion strength;
[0093] Step S5: Mix 10 g of Ecoflex 00-30 silicone rubber with 1 g of a curing agent (Ecoflex is a two-component, component A is silicone rubber, and component B is a curing agent), add 44 g of tetrahydrofuran, and stir for 30 min until evenly mixed;
[0094] The LCE fibers with a wrinkled metal coating obtained in step S4 were immersed in the above Ecoflex solution at a speed of 0.5 mm / s, and after 30 seconds, they were evenly lifted; they were cured at room temperature for 24 h to form a waterproof protective layer with a thickness of about 80 μm, and the subsurface modified and enhanced conductive liquid crystal elastomer fibers (denoted as LCE composite fibers) were obtained.
[0095] Examples 2 - 3
[0096] The differences from Example 1 are only that the electroless deposition time of the metal is different. The electroless deposition times of the metal in Examples 2 and 3 are 60 min and 10 min respectively.
[0097] Example 4
[0098] Step S1: 19.4 g of RM257, 2.9 g of PETMP, 2.7 g of HDT and 75.3 g of dichloromethane were stirred at room temperature for 2 h to obtain a mixed solution. Then 5.17 g of an ATRP initiator (BrMA), 1.2 g of DPA and 2 g of HHMP were added, and the mixture was stirred for 15 min. It was extruded through a spinning needle (the needle aperture was 0.6 mm) at 80 °C, and the fibers were cured and formed and collected on a PTFE roller (dichloromethane evaporated). Then, secondary cross-linking was carried out under ultraviolet light irradiation and a specific stretching multiple (365 nm, 2.5 times, 3 min) to obtain LCE fibers containing an ATRP initiator.
[0099] Steps S2 - S5 are the same as those in Example 1.
[0100] The as-prepared primary LCE fibers in Example 1 are as Figure 2 and Figure 3 shown, where Figure 2 is the scanning electron microscope image, Figure 3 is the POM image of the primary LCE fibers. The SEM image of the LCE composite fibers prepared in Example 1 is as Figure 4 shown, where the upper figure is the actual scanning electron microscope picture, and the lower figure is the energy spectrum diagram (EDS) of copper element of the scanning electron microscope. It can be seen from Figures 2 to 4 that the copper nanoparticles are evenly and continuously attached to the surface of the liquid crystal elastomer fibers.
[0101] Figure 5 is the SEM image of the LCE composite fibers prepared in Example 2 (the electroless deposition time of the metal is 60 min), Figure 6SEM image of the LCE composite fiber prepared in Example 3 (electroless metal deposition time is 10 min). The upper figure is the actual SEM image, and the lower figure is the energy spectrum diagram (EDS) of copper element of the SEM. Different electroless metal deposition times will result in different thicknesses of the wrinkled metal coating, thereby affecting the performance of the LCE composite fiber. In Example 1, 120 min of electroless metal deposition was carried out, and the formed wrinkled metal coating completely covered the fiber, with good conductivity and good driving strain performance.
[0102] Figure 7 The maximum braking strain diagram of the LCE composite fiber prepared in Example 1 under different voltages (electrical drive) when loading a 5.5 g weight; as the voltage increases, the strain increases because the applied voltage generates Joule heat, causing the LCE composite fiber to contract.
[0103] Figure 8 The braking strain diagram of the LCE composite fiber prepared in Example 1 at different temperatures; the LCE composite fiber can reach a maximum driving strain of about 45% as the temperature increases. The LCE composite fiber has higher reversible driving controllability under electrical stimulation, faster response speed, and shorter driving time. More importantly, the driving under electrical stimulation can integrate the sensing function and output the motor signal outward, making the controllability of its driving state higher.
[0104] Figure 9 The result diagram of the LCE composite fiber prepared in Example 1 cycled 500 times under electrothermal drive at 20 V and 0.1 s. It can be seen that the resistance change rates are not much different, proving that the sub-surface modified enhanced conductive liquid crystal elastomer fiber of the present invention has good stability.
[0105] The preparation method of the sub-surface modified enhanced conductive liquid crystal elastomer fiber of the present invention grafts a polymer brush on the sub-surface of the fiber. The metal conductive layer forms a strong interfacial bond with the fiber matrix through the embedded polymer brush, endowing the modified (sub)-surface layer of the fiber with better mechanical properties. And after the modified sub-surface layer is damaged, it can be polymerized and modified repeatedly without initiator modification and assembly. At the same time, based on the dynamic bridging effect of metal particles at the wrinkled structure, the fiber can achieve rapid response and sensitive sensing. After multiple driving cycles, it still exhibits excellent driving performance, high conductivity, and good mechanical properties. In addition, an Ecoflex waterproof layer is added on the surface of the wrinkled metal coating, which can effectively isolate environmental moisture and electrolytes, prevent the electrochemical corrosion of the metal coating, and at the same time, maintain the original driving performance of the fiber and will not significantly affect the deformation ability of the LCE fiber. The sub-surface modified enhanced conductive liquid crystal elastomer fiber of the present invention performs excellently in terms of driving performance, interfacial stability, and functional integration. The present invention provides important technical support for the research and application in related fields.
[0106] Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments according to the embodiments of the present invention without creative work, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A preparation method of a subsurface-modified enhanced conductive liquid crystal elastomer fiber, characterized in that, It includes the following steps: Mix a liquid crystal monomer, a crosslinking agent, a spacer, a nonpolar solvent, an atom transfer radical polymerization initiator, an amine catalyst, and a photoinitiator to conduct a first crosslinking reaction. Remove the solvent from the obtained first crosslinking reaction solution, and conduct a second crosslinking reaction under ultraviolet light irradiation and stretching to obtain a liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator; Under a protective atmosphere, mix the liquid crystal elastomer fiber containing an atom transfer radical polymerization initiator, methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, CuBr, and methanol to conduct an atom transfer radical polymerization reaction to obtain a liquid crystal elastomer fiber with a subsurface grafted polymer brush; Perform ion exchange on the liquid crystal elastomer fiber with a subsurface grafted polymer brush in an ammonium tetrachloropalladate solution to obtain a liquid crystal elastomer fiber with active sites on the surface; Perform electroless metal deposition on the liquid crystal elastomer fiber with active sites on the surface to obtain a liquid crystal elastomer fiber with a wrinkled metal coating; Coat an Ecoflex waterproof layer on the surface of the liquid crystal elastomer fiber with a wrinkled metal coating to obtain a subsurface modified enhanced conductive liquid crystal elastomer fiber.
2. The preparation method according to claim 1, characterized in that, The mass of the atom transfer radical polymerization initiator is 3% - 8% of the total mass of the liquid crystal monomer, crosslinking agent, spacer, nonpolar solvent, amine catalyst, and photoinitiator.
3. The preparation method according to claim 1, wherein The temperature of the atom transfer radical polymerization reaction is 50 - 70 °C, and the time is 4 - 5 h.
4. The preparation method according to claim 1 or 3, characterized in that, The dosage ratio of methacryloyloxyethyl trimethyl ammonium chloride, 2,2-bipyridine, and CuBr is 5 mL: 126 - 128 mg: 67 - 68 mg.
5. The preparation method according to claim 1, characterized in that, The ion exchange in the ammonium tetrachloropalladate solution is as follows: soak the liquid crystal elastomer fiber with a subsurface grafted polymer brush in the ammonium tetrachloropalladate solution; the concentration of the ammonium tetrachloropalladate solution is 5 - 10 mmol / L, and the soaking time is 2 - 6 h.
6. The preparation method according to claim 1, characterized in that, The electroless metal deposition is as follows: soak the liquid crystal elastomer fiber with active sites on the surface in a metal solution; the metal solution includes a copper electroless plating solution, a nickel electroless plating solution, a silver electroless plating solution, or a gold electroless plating solution; the soaking time is 30 - 180 min.
7. The preparation method according to claim 6, characterized in that, The copper electroless plating solution includes solution A and solution B. Solution A includes: 13 g / L copper sulfate pentahydrate, 29 g / L sodium potassium tartrate, 12 g / L sodium hydroxide, and 1 g / L dimethylaminoborane; solution B is an aqueous formaldehyde solution with a mass fraction of 0.35 - 0.38%; the volume ratio of solution A to solution B is 1:
1.
8. The preparation method according to claim 1, characterized in that The coating of the Ecoflex waterproof layer is as follows: immerse the liquid crystal elastomer fiber with a wrinkled metal coating in the Ecoflex solution, lift it, and cure it; The solid content of the Ecoflex solution is 18% - 22%.
9. The subsurface-modified enhanced conductive liquid crystal elastomer fiber obtained by the preparation method according to any one of claims 1 to 8, characterized in that, It includes a liquid crystal elastomer fiber, a polymer brush grafted on the subsurface of the liquid crystal elastomer fiber, and a wrinkled metal coating and an Ecoflex waterproof layer sequentially arranged on the surface of the polymer brush.
10. Application of the subsurface modified enhanced conductive liquid crystal elastomer fiber according to claim 9 in a soft robot.